Incidence of PJI in Total Knee Arthroplasty Patients Following Expanded Gram-Negative Antibiotic Prophylactic Protocol - Anzar Sarfraz; Cameron Bussey-Sutton; Emily M. Ronan; Farouk Khury; Joseph A. Bosco; Ran Schwarzkopf; Vinay K. Aggarwal (Microorganisms)
The efficacy of “Expanded Gram-Negative Antimicrobial Prophylaxis” (EGNAP) in preventing postoperative infections has been previously reported in total hip arthroplasty (THA). However, it remains unclear as to whether these benefits extend to total knee arthroplasty (TKA). This study investigated whether adding EGNAP to our institution’s preoperative antibiotic prophylaxis protocol would affect periprosthetic joint infection (PJI) risk in TKA patients. We retrospectively reviewed 10,666 elective, unilateral, primary TKA cases performed at a single-specialty tertiary academic hospital from 2018 to 2022. Before June 2021, all patients received 2 g of cefazolin for 24 h as part of the prophylactic antibiotic protocol. After June 2021, gentamicin or aztreonam (EGNAP) was added to the protocol for all TKA patients. Patients were grouped based on whether they received EGNAP or not (control group) before surgery. The groups were propensity score-matched in a 2:1 ratio. PJI and nephrotoxicity (using RIFLE criteria) risk was compared. After matching, the final study population consisted of 3007 patients in the non-EGNAP group and 1503 patients in the EGNAP group. There was no significant difference between the EGNAP and no EGNAP groups in the overall incidence of PJI (1.9% vs. 2.0%; p = 0.111) or the incidence of Gram-positive PJIs (0.3% vs. 0.8%; p = 0.103). The incidence of Gram-negative PJIs was 0.5% in the EGNAP group and 0.4% in the no EGNAP group, which was also not different between the groups (p = 0.692). There were no differences in nephrotoxicity between groups (p = 0.521). The addition of EGNAP to the antibiotic prophylactic protocol prior to TKA had no effect on overall or Gram-negative PJI risk in TKA patients. The findings of this study suggest that while EGNAP is safe to use and has minimal nephrotoxic effects, its prophylactic benefits do not extend to the primary TKA population. This may be attributed to the generally low rate of Gram-negative infections in TKA patients, where adding EGNAP does not provide a clear advantage in reducing the risk of such infections, unlike its potential benefits in primary THA population. This study investigates the effects of using prophylactic Gram-negative antibiotics prior to TKA and shows that though it is safe to use, Gram-negative bacterial coverage may have no impact on postoperative infection incidence.